ITIL 4 digital and IT strategy (DITS) your companion to the ITIL 4 Strategic Leader DITS certification - Agutter, Claire (IT Governance Publishing, 2024)
This guide contains everything you need to know to pass the ITIL 4® Strategic Leader Digital and IT Strategy certificate, plus more. It covers practices and concepts that are not addressed as part of the DITS syllabus, making it ideal for newly qualified practitioners.